DESIGN OF ARABIC CURRICULUM DEVELOPMENT BASED ON CHARACTER EDUCATION - Mohammad Misbahul Munir; Syamsul Anam; Faisol Nasar Bin Madi (Advances In Social Humanities Research, 2023)
Arabic has a position of great importance for Muslims, not only the language of religion (the Qur'an) but also Arabic as a science that needs to be developed. Especially in building a character-based curriculum, where the enthusiasm of today's children decreases, especially in character to continue to grow. Students must meet global standards. The purpose of this study is to describe how to develop an Arabic learning curriculum by shaping the personality or character of students. Development of Arabic curriculum at MTS Al-Ishlah Jenggawah. At MTS Al-Ishlah, curriculum development is carried out through: (1) routine activities in Arabic, (2) examples of educators and education staff in teaching and preparing learning tools, (3) creating a good Arabic language environment. The results showed that the development of a character-based Arabic curriculum can be achieved through: integration of personality values into Arabic subjects, self-development programs, creating an ethical system and values in schools, implementing values and ethics in Arabic language learning by applying different approaches and methods and strategies